Separation of ischiopagus tetrapus conjoined twins in Dr. Sardjito Hospital, Yogyakarta - Rochadi Rochadi (Paediatrica Indonesiana, 2008)
This paper reports a case of conjoined twinswho were successfully separated in Sardjito Hospital,Yogyakarta, Indonesia in 2006.